T cell-derived exosomes in tumor immune modulation and immunotherapy - Zhou, Qiujun; Wei, Shenyu; Wang, Hui; Li, Yuanyuan; Fan, Shasha; Cao, Yi; Wang, Chenglei (Frontiers in Immunology, 2023)
Exosomes are nanoscale vesicles secreted by most cells that have a phospholipid bilayer structure. Exosomes contain DNA, small RNA (sRNA), proteins and other substances, which can carry proteins and nucleic acids and participate in the communication between cell. T cells are an indispensable part of adaptive immunity, and the functions of T cell-derived exosomes have been widely studied. In the more than three decades since the discovery of exosomes, several studies have revealed that T cell-derived exosomes play a novel role in cell-to-cell signaling, especially in tumor immune response. In this review, we will review the function of exosomes derived from different T cell subsets, explore applications in tumor immunotherapy and consider the associated challenges.